Re-examining judicial review of delegated legislation - CHNG, Wei Yao, Kenny (Institutional Knowledge at Singapore Management University, 2023)
The usage of delegated legislation as a means of governance deserves significant attention, in view of the enormous impact that it is capable of having on the lives of citizens. While reforms to the process of parliamentary scrutiny are an important means of minimising the inappropriate usage of delegated legislation, this paper explores the possibility of drawing more fruitfully upon judicial review as an additional control mechanism. It undertakes a theoretical analysis of what makes delegated legislation distinct from primary legislation and other types of executive action for the purposes of judicial review, with a view towards identifying the proper normative orientation of judicial review of delegated legislation – upholding the moral requirements of delegation relationships and safeguarding democratic accountability and the rule of law. It then argues that existing grounds of review applied towards delegated legislation go some way towards but are inadequately directed at this normative orientation. Drawing inspiration from Irish and US jurisprudence, the paper critically evaluates several possible means of filling this doctrinal space, and concludes that the non-delegation doctrine and a rule of law-based ground of judicial review directed at exercises of delegated law-making power can supplement the law of judicial review of delegated legislation.